2015
DOI: 10.1007/s12020-015-0733-4
|View full text |Cite
|
Sign up to set email alerts
|

Distinct effects of dipeptidyl peptidase-4 inhibitor and glucagon-like peptide-1 receptor agonist on islet morphology and function

Abstract: Although the two anti-diabetic drugs, dipeptidyl peptidase-4 inhibitors (DPP4is) and glucagon-like peptide-1 (GLP-1) receptor agonists (GLP1RAs), have distinct effects on the dynamics of circulating incretins, little is known of the difference in their consequences on morphology and function of pancreatic islets. We examined these in a mouse model of β cell injury/regeneration. The model mice were generated so as to express diphtheria toxin (DT) receptor and a fluorescent protein (Tomato) specifically in β cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Experimental evidence indicated that GLP-1 receptor agonists enhance b-cell proliferation and prevent b-cell apoptosis. [18,24,26,43]. Moreover, it was reported that liraglutide did not affect islet endocrine non-b-cells.…”
Section: Discussionmentioning
confidence: 98%
“…Experimental evidence indicated that GLP-1 receptor agonists enhance b-cell proliferation and prevent b-cell apoptosis. [18,24,26,43]. Moreover, it was reported that liraglutide did not affect islet endocrine non-b-cells.…”
Section: Discussionmentioning
confidence: 98%
“…In the current study, the majority of patients received second-line treatment with a mode of action different from the first as recommended by Japanese treatment guidelines [4]. The higher use of DPP4is as the first-or the second-line agent in the current study (84.7%) may reflect various favorable characteristics of this class of agent in the clinical practice of diabetes care, including low risk of hypoglycemia and weight gain [2,19], safety (at reduced doses) in patients with renal failure [21], cytoprotective effects on pancreatic b-cells [22], and improved glycemic stability [23]. In addition, compared with Caucasians, Japanese patients with T2DM appear to be more predisposed to impaired insulin secretion rather than increased insulin resistance [6,24], Therefore, Japanese patients may receive greater benefit from DPP4is, which increase the endogenous incretin levels and promote insulin secretion in a glucose-dependent manner.…”
Section: Discussionmentioning
confidence: 88%
“…In a retrospective study in Korea, metformin and DPP4i was found to be effective in reducing HbA1c below 7%, with a low incidence of hypoglycemia [ 92 ].In tacrolimus-induced SD rat model and nephrotoxicity test, DPP4i and sodium–glucose transporter 2 inhibitors (SGLT2i) reduced blood glucose level and HbA1C level, and increased plasma insulin level and islet size of rats, and improved renal function and reduced interstitial fibrosis and pro-fibrotic cytokines, which providing a theoretical basis for the combination of SGLG2i and DPP4i in the treatment of tacrolimus-induced DM and nephrotoxicity [ 93 ]. The dual effect of DPP4i on α- and β- cells means that they also bind well to the islet independence of SGLT2i [ 94 ]. In addition, when DPP4i is combined with insulin secretin or insulin itself, DPP4i provides a complementary effect due to its inhibition of glucagon secretion and reduction in hepatic glucose production, which also means that a beneficial effect on glucose control can be achieved even with reduced β cell function [ 94 ].…”
Section: Dpp4 and Dpp4 Inhibitions In Diabetesmentioning
confidence: 99%
“…The dual effect of DPP4i on α- and β- cells means that they also bind well to the islet independence of SGLT2i [ 94 ]. In addition, when DPP4i is combined with insulin secretin or insulin itself, DPP4i provides a complementary effect due to its inhibition of glucagon secretion and reduction in hepatic glucose production, which also means that a beneficial effect on glucose control can be achieved even with reduced β cell function [ 94 ]. In Chinese trials with T2DM, the addition of linagliptin and insulin improved glycemic control and was well tolerated with no increased risk of hypoglycemia or weight gain [ 95 ].…”
Section: Dpp4 and Dpp4 Inhibitions In Diabetesmentioning
confidence: 99%